2012
DOI: 10.1002/qj.2032
|View full text |Cite
|
Sign up to set email alerts
|

A coupled energy transport and hydrological model for urban canopies evaluated using a wireless sensor network

Abstract: We propose a new surface exchange scheme coupling the transport of energy and water in urban canopies. The new model resolves the subfacet heterogeneity of urban surfaces, which is particularly useful for capturing surface exchange processes from vegetated urban surfaces, such as lawns or green roofs. We develop detailed urban hydrological models for surfaces consisting of either natural (soil and vegetation) or engineered materials with water-holding capacity. The coupling of energy and water transport enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 193 publications
(150 citation statements)
references
References 54 publications
1
145
0
Order By: Relevance
“…The effect of the built-up environment manifests itself by impacting turbulent transport radiative heat exchange and hydrological processes, especially in urban canopies [36]. Schatz and Kucharik also demonstrated in their paper that the built-up environment was the primary driver of the spatial change in temperature patterns in the urban area [37].…”
Section: Discussionmentioning
confidence: 97%
“…The effect of the built-up environment manifests itself by impacting turbulent transport radiative heat exchange and hydrological processes, especially in urban canopies [36]. Schatz and Kucharik also demonstrated in their paper that the built-up environment was the primary driver of the spatial change in temperature patterns in the urban area [37].…”
Section: Discussionmentioning
confidence: 97%
“…To do this, one group of models having particularly promising potential is the urban land surface modeling schemes, the so-called urban canopy models (UCMs) developed in the widely-used Weather Research and Forecasting (WRF) platform [101,102] by the National Center for Atmospheric Research (NCAR). The most common urban land surface models in WRF are the single layer [103][104][105][106][107] and the multi-layer UCMs [108][109][110][111]. WRF-UCM system integrates the physics of energy and mass transport in the urban canopy layers and the mesoscale atmospheric dynamics, thus provides a versatile modeling framework for multi-scale numerical simulations ranging from building to regional scales.…”
Section: Impact Of Reflective Materials On Building Energy Consumptionmentioning
confidence: 99%
“…In addition, a posteriori analysis of surface energy budgets found that only 1 % of the residual variance can be attributed to advection and is not statistically significant (Higgins, 2012). The turbulent sensible and latent heat fluxes arising from the urban area (H u and LE u ) are the areal average of those from roofs (H R and LE R ) and the street canyon (H can and LE can ) (Wang et al, 2013):…”
Section: Coupled Urban Land-atmospheric Modelmentioning
confidence: 99%
“…In this paper, urban land-atmosphere interactions are modeled using a 1-D stand-alone and scalable numerical framework (Song and Wang, 2015a), by coupling an advanced single layer urban canopy model (SLUCM) for urban land surface processes (Wang et al, 2011b;Wang et al, 2013) and a single column model (SCM) for boundary layer dynamics (Noh et al, 2003;Troen and Mahrt, 1986). To single out the direct impact of urban landscape modification, we test the sensitivity of the boundary layer only in the vertical direction without taking advection effect into consideration.…”
Section: Coupled Urban Land-atmospheric Modelmentioning
confidence: 99%
See 1 more Smart Citation